Performance skills of Grade 1 learners: educators' knowledge and attitude - Vermaas, Susanna Helena (University of the Free State, 2010)
South African children’s performance in reading, numeracy and writing performance is well below expected levels. In the Quality Improvement, Development, Support and Upliftment Programme Baseline Study (QIDS-UP) conducted in the Free State in March 2008, the results for the Grade 3s in respect of literacy and numeracy were 43,32% and 38,24% respectively. There are a myriad of reasons why learners are unable to read and write, among which educators’ knowledge and attitudes could be contributing factors. A significant conceptual change to the Inclusive Education System is the early identification of learners with barriers, such as developmental delays, and the subsequent support of such learners. Developmental delays can become evident in writing, numeracy and reading deficits in scholastic tasks. Occupational therapists do not remediate the reading or writing delays, but assess a child to determine the underlying performance skills delays that cause the scholastic problem. Currently, there is only one occupational therapist working for the Free State Department of Education at the district level. An effective means of delivering occupational therapy services within this particular context would be to empower educators to identify, manage and support learners who demonstrate poor performance skills. This research attempted to determine educators’ knowledge and attitudes regarding the age-appropriate performance skills of a typical Grade 1 learner. This was a cross-sectional study involving a stratified, randomly selected sample of 48 of the 257 schools in the Motheo District. All the Grade 1 educators at the selected schools were requested to complete a questionnaire designed by the researcher. The questionnaire was developed by considering the age-appropriate performance skills that underlie the scholastic skills of a Grade 1 learner and further by extracting the associated Grade 1 outcomes from the National Curriculum Statement with which educators are familiar. This research focused on the following components: gross-motor, fine-motor and cognitive skills. Educators’ attitudes regarding behavioural, cognitive and affective aspects were determined. The sample comprised 117 educators of whom 47,3% had completed their training more than 20 years before. Only 18,8% had a four-year qualification, the minimum requirement for educators. The mean age of the participants was 46,6 years. The mean for Grade 1 teaching experience was 88 months, while the median for Foundation Phase teaching experience was 16,6 years. The mean number of learners per class was 42 (ranging between 21 and 67). The medians of the total correct scores for knowledge regarding gross-motor skills, fine-motor skills and cognitive skills were 25,0%, 25% and 28,6% respectively. There were 2,6% who could not answer any questions correctly and 91,5 % of the educators scored below 46,7% on the composite knowledge score. The highest score (66,7%) was obtained by 2,6% of the educators. Educators were found to have a generally positive attitude in respect of support to learners experiencing performance-skills delays (mean = 80,0%). Relationships were determined between training, experience, knowledge and attitude. It was evident that as the number of years of training increased, so attitude improved (p=0.0321). No relationship was apparent between training and knowledge, nor between experience and knowledge or attitude. The poor scores for the identification of motor and cognitive skills could indicate that educators will not be able to identify learners with barriers in their classes. The exceptionally positive attitudes found among educators could have resulted from this lack of knowledge, which, in turn, led to skewed perceptions regarding the demands of teaching learners with barriers and developmental delays. These findings will guide the researcher to develop educator-friendly and purposeful training that will empower educators to identify and support learners who present with delays in development. The important role that the occupational therapist at the district level should play in supporting educators and learners to embrace inclusive practices was also emphasised.

Die lees-, skryf en gesyferdheidsvaardighede van Suid-Afrikaanse leerders is ver onder die vereiste standaarde. Volgens ʼn opname in 2008 – die “Quality Improvement, Development, Support and Upliftment Programme Baseline Study” (QIDS-UP) – was Graad 3-leerders in die Vrystaat se geletterdheids- en gesyferdheidsvaardighede onderskeidelik 43,32% en 38,24%. Daar is verskeie faktore wat bydra tot leerders se onvermoë om te kan lees en reken, waaronder onderwysers se kennis en houdings. ʼn Belangrike konseptuele verandering na Inklusiewe Onderwys is die vroeë identifisering en hantering van leerders met leerhindernisse, soos ontwikkelingsagterstande, asook die ondersteuning van sodanige leerders. Ontwikkelingsagterstande kan manifesteer in agterstande ten opsigte van lees-, skryf- en rekenvaardighede. Arbeidsterapeute spreek nie die lees- en skryfagterstande aan nie, maar bepaal die onderliggende vaardigheidsgebreke wat aanleiding gee tot die leerder se swak skolastiese prestasie. Tans is daar net een arbeidsterapeut werksaam op die distriksvlak in die Vrystaatse Departement van Onderwys. Een van die doeltreffende wyses van dienslewering in hierdie konteks is om onderwysers te bemagtig om leerders wat probleme ondervind met die uitvoer van aktiwiteitsverrigtingsvaardighede te identifiseer en te ondersteun. Hierdie navorsing was daarop gemik om onderwysers se kennis van en houdings omtrent die ouderdomstoepaslike aktiwiteitsverrigtingvaardighede van ʼn tipiese Graad 1-leerder te bepaal. Hierdie dwarssnitstudie het ʼn gestratifiseerde, ewekansig-geselekteerde groep van 48 van die 257 skole in die Motheo-distrik behels. Al die Graad 1-onderwysers van die geselekteerde skole is versoek om ʼn vraelys – deur die navorser opgestel – te voltooi. Die vraelys is ontwikkel na aanleiding van ʼn ondersoek van die onderliggende skolastiese/ontwikkelingsvaardighede van ʼn tipiese Graad 1-leerder, asook die geassosieerde vaardighede soos beskryf in die Nasionale Kurrikulumverklaring waarmee onderwysers bekend is. Die volgende komponente is afgebaken: groot motoriese vaardighede, fyn motoriese vaardighede en kognitiewe vaardighede. Houding t.o.v. affektiewe, gedrag en kognitiewe response is bepaal. Van die studiepopulasie van 117 het 47,3% van die onderwysers hul kwalifikasies meer as 20 jaar vantevore voltooi. Slegs 18,8% beskik oor ʼn vier-jaar onderwyskwalifikasie – die minimum kwalifikasievereiste vir onderwysers. Die gemiddelde ouderdom van die deelnemers was 46,6 jaar, hulle het ʼn gemiddeld van 88 maande ondervinding van Graad 1-onderrig gehad en die mediaan ten opsigte van onderrigervaring in grondslagfase-onderwys was 16,6 jaar. Die gemiddelde aantal leerders per klas was 42 (reikwydte 21 to 67). Die mediaan vir die korrekte kennistotale ten opsigte van groot motoriese vaardighede, fyn motoriese vaardighede en kognitiewe vaardighede was onderskeidelik 25,0%, 25% en 28,6%. Daar was 2,6% van die onderwysers wat geen vrae korrek beantwoord het nie en 91,5% van die onderwysers het minder as 46,7% behaal met die berekening van die totale kennis. Die hoogste kennistelling was 66,7% en is behaal deur 2,6% van die onderwysers. Onderwysers het ʼn algemene positiewe houding geopenbaar in verband met die ondersteuning van leerders met agterstande ten opsigte van aktiwiteitsverrigtingsvaardighede (gemiddeld = 80,0%). Verbande tussen opleiding, ondervinding, kennis en houdings is bepaal. Dit was opmerklik dat soos die aantal jare opleiding vermeerder het, het houding verbeter (p=0.0321). Geen verband is tussen opleiding en kennis of tussen ondervinding en kennis en houding bevind nie. Die swak kennistellings kan ʼn aanduiding wees dat onderwysers nie in staat/bekwaam is om tipiese agterstande by Graad 1-leerders te identifiseer nie. Onderwysers se uiters positiewe houding kan moontlik toegeskryf word aan hul verdraaide persepsies – vanweë gebrekkige kennis – van wat die eise van leerders met tipiese ontwikkelingsagterstande behels. Die bevindige van hierdie studie kan ʼn spesifieke bydrae lewer om die rol van die arbeidsterapeut op distriksvlak – soos die geval in hierdie studie – te definieer. Die bevindinge kan die navorser lei om gebruikersvriendelike en doelmatige opleiding te ontwikkel sodat onderwysers bemagtig kan word om leerders met agterstande te identifiseer en ondersteun.
Dissertation (M. Occupational Therapy (Occupational Therapy))--University of the Free State, 2010
Keywords: Occupational therapy for children; Inclusive education -- South Africa; Teachers -- Attitudes; Inclusive Education; Occupational therapy; Cognitive skills; Fine-motor skills; Gross-motor skills; Performance skills; Attitude; Educators; Knowledge